Augustinian Piety and Catholic Reform: Augustine, Colet, and Erasmus - Peter Iver Kaufman (USA Mercer University Press, 1982)
$9.45
Keywords: Dogmatic Theology (3GddGghJ GdYbjOjs; Salvation -- Christianity -- History of doctrines; Reformation -- Early movements